COMPARISION OF STAINLESS STEEL, EPOXY GLASS BALL BEARING AND CAST NYLON BUSH FOR OPTIMIZATION OF NATURAL FREQUENCY WITH THE HELP OF FEM - Savaliya, Vishal V; Mendapara, Hitesh; Savaliya, Ajay; Chalodiya, Pushpak; Jankar, Sunil; Patel, Jignesh (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
According to GTU for industry define problem (IDP) , We visited " Meera Industry pvt. Ltd." situated at SACHIN GIDC, SURAT .This is about two for one yarn twister machine (TFO machine).In two for one twister yarn ( thread twisting ) machine ,There is major problem of vibration in machine due ti high speed of gears with cams ans also problem is wearing quickly of bushing material contacted with rotating cams in Gear box because of high speed of cam and high friction of bush and we have to replace in a time . By this problem we have suggested a solution to change a better material instead of current bushing material element. For it we will design in PRO E and analysis in ANSYS of diffrent materials. Through comparision of numerical analysis data of different materials we will choose better material elements instead of current bushing material. This will help in the problem of wear out of the bush in machine with suitable root cause we will solve this problem in two for one yarn twister machine in which bushing material has developed because of its combination of low coefficient of friction with self-lubricating properties, good mechanical properties and dimensional stability